Five-Year Clinical Outcome of the Biodegradable Polymer Ultrathin Strut Sirolimus-Eluting Stent Compared to the Biodegradable Polymer Biolimus-Eluting Stent in Patients Treated With Percutaneous Coronary Intervention: From the SORT OUT VII Trial. (17th January 2023) - Hansen, Kirstine Nørregaard; Jensen, Lisette Okkels; Maeng, Michael; Christensen, Martin Kirk; Noori, Manijeh; Kahlert, Johnny; Jakobsen, Lars; Junker, Anders; Freeman, Phillip; Ellert-Gregersen, Julia; Raungaard, Bent; Terkelsen, Christian Juhl; et al.
Abstract : Background: Biodegradable polymer drug-eluting stents were developed to improve safety and efficacy outcomes for patients undergoing percutaneous coronary intervention. However, few long-term follow-up efficacy studies are available. The study sought to investigate 5-year results from the SORT OUT VII trial (Scandinavian Organization for Randomized Trials With Clinical Outcome) comparing the biodegradable polymer ultrathin-strut sirolimus-eluting Orsiro stent (O-SES) versus the biodegradable polymer biolimus-eluting Nobori stent (N-BES). Methods: This registry-based, randomized, multicenter, single-blinded, noninferiority trial compared O-SES and N-BES in an all-comer population. The composite primary end point, target lesion failure, consisted of cardiac death, myocardial infarction related to the target lesion, or target lesion revascularization within 1 year. Follow-up was extended to 5 years. Results: Five-year follow-up was completed for 2521 patients (99.8%). Five-year target lesion failure did not differ between O-SES (12.4%) and N-BES (13.1%; rate ratio [RR], 0.94 [95% CI, 0.75–1.18]). Cardiac death (RR, 0.95 [95% CI, 0.67–1.34]), target myocardial infarction (RR, 1.14 [95% CI, 0.76–1.71]), target lesion revascularization (RR, 0.90 [95% CI, 0.67–1.21]), and definite stent thrombosis rates (RR, 0.73 [95% CI, 0.41–1.33]) did not differ significantly between the 2 stents. Within the first year, definite ST was significantly lower for O-SES (0.4%) compared to N-BES (1.2%; RR, 0.33 [95% CI, 0.12–0.92]), but no difference was from 1 through 5 years: O-SES 1.2% and N-BES 0.9% (RR, 1.28 [95% CI, 0.58–2.82]). Conclusions: Five years after treatment with biodegradable polymer stents, target lesion failure did not differ among O-SES and N-BES. Definite stent thrombosis was less often seen within the first year in the O-SES but the difference was not maintained after 5 years. Registration: URL: https://clinicaltrials.gov ; Unique identifier: NCT01879358.